Irrigation management strategy for Prata-type banana - Marcelo R. dos Santos; Sérgio L. R. Donato; Lilian L. Lourenço; Tânia S. Silva; Mauricio A. Coelho Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to analyze different irrigation strategies in two cultivars of the banana crop. The study was conducted in four production cycles of ‘Prata-Anã’ and ‘BRS Platina’ bananas. The applied irrigation depths (ID) were obtained by the model ID = K x LA x ETo, where K is an empirical transpiration constant of 0.20; 0.35; 0.50 and 0.65 for the strategies 1, 2, 3 and 4, respectively; LA is the leaf area of mother and daughter plants of ‘Prata-Anã’ and ETo is the reference evapotranspiration. The strategy 5 was obtained according to the crop evapotranspiration, ETc = ETo x Kc, where Kc is the crop coefficient. Drip irrigation system was used, with two laterals per plant row and emitters with flow rate of 8 L h-1, spaced at 0.50 m. It was found that ‘Prata-Anã’ is more efficient than ‘BRS Platina’ in terms of water use and the model for irrigation management, ID = 0.35 x LA x ETo, is recommended to optimize water use by ‘Prata-Anã’ and ‘BRS Platina’ bananas, with increase in water use efficiency and maintenance of yield. The same model, with K coefficient equal to 0.50, makes it possible to obtain yield and water use efficiency equal to those obtained with irrigation management based on the ETc.